THU0572 Adherence to Disease Modifying Anti-Rheumatic Drugs in Patients with Rheumatoid Arthritis: A Qualitative Study in Two Ethnic Groups. (23rd January 2014) - Kumar, K.; Raza, K.; Gill, P.; Greenfield, S.
Abstract : Background: Rheumatoid arthritis (RA) is a common disabling condition. Although highly effective drugs are available for its treatment, poor adherence remains a significant problem. Several studies have shown ethnic group differences in the way that medications are viewed. 1 ;2 These views may have a detrimental effect on RA medication adherence 3 . Objectives: To explore factors influencing adherence amongst RA patients of White and South Asian origin. Methods: A purposeful sample of participants was identified from our cohort recruited from hospital clinics. In total 20 White and South Asian participants with RA (10 good and 10 poor adherers as determined by responses to the Medication Adherence Report Scale) participated. In-depth semi-structured interviews were performed until data saturation was reached. Interviews were transcribed and analysed using a constant comparative method to identify themes. Results: 13 out of 20 were females (mean age of all patients 41 years). Four interlinking themes influenced adherence in the two ethnic groups: [i] Symptom severity. [ii] Illness Perception (IPQ). [iii] Beliefs about medicines. [iv] The quality and quantity of information. Reasons for good adherence were similar in individuals from the two ethnic groups. Participants who had experienced severe symptoms reported better adherence. They accepted that the disease was a long term condition and agreed that managing it required lifelong therapy. A key factors motivating participants to adhere to DMARDs were having received an ultrasound joint scan and discussions about disease measure parameters. These gave them a good understanding of the disease process so that they were clear about the need for long term therapy. While none of the poor adherers (White or South Asian) had received an ultrasound joint scan. Amongst the poor adherers there were differences in reasons for poor adherence between participants from the two ethnic groups. In particular, poorly adhering South Asians participants viewed their disease to be short term and did not believe that long term therapy was needed. Furthermore, they did not view RA as a "serious" disease. In contrast, the poorly adhering White participants often modified doses of DMARDs dependent on their symptomatology. Conclusions: There were many similarities amongst reasons for good adherence in RA participants from the two ethnic groups studied. However, clear differences were seen amongst the poor adherers. The potential use of an ultrasound intervention may help to improve patients' understanding of the disease and promote better adherence to DMARDs in patients with RA. References: Reference List Kumar K, Gordon C, Toescu V, et al . Beliefs about medicines in patients with RA and SLE: a comparison between patients of South Asian and White British origin. Rheumatology 2008; 47 ((5):):690-697. Kumar K, Gordon C, Barry R, et al . 'It's like taking poison to kill poison but I have to get better': a qualitative study of beliefs about medicines in Rheumatoid arthritis and Systemic lupus erythematosus patients of South Asian origin. Lupus 2011; 20(8):837-844. Salt E, Frazier SK. Adherence to disease-modifying antirheumatic drugs in patients with rheumatoid arthritis: a narrative review of the literature. Orthop Nurs 2010; 29(4):260-275. Disclosure of Interest: None Declared